Comparative in vitro imunotoxicology of acyclovir and other antiviral agents. - Steele, R W (1980)
In vitro lymphocyte blastogenic responses to the commonly employed mitogens phytohemagglutinin, pokeweed, and concanavalin A were evaluated when acyclovir, adenine arabinoside, cytosine arabinoside, and idoxuridine were added to the culture materials. Similarly, specific antigen-induced blastogenic responses, including herpes group antigens, and cytotoxicity and leukocyte inhibitory factor assays with herpes group viruses were determined in the presence and absence of antiviral agents. No depression of these cellular immmune responses by acyclovir or adenine arabinoside ws demonstrated. This was in contrast to the effects of cytosine arabinoside and idoxuridine, which severely inhibited blastogenic and cytotoxic responses but not leukocyte inhibitory factor production. Even at concentrations up to 20 microgram/ml, the antiviral agent acyclovir did not depress selected cellular immune responses that are important for successful elimination of invading herpes group viruses.